Comparative evaluation of the degree of conversion of an 8th-generation bonding agent when applied to normal dentin or caries-affected dentin, pre-treated with MMP inhibitors – An in vitro study - Neil Vincent Lewis; Shalini Aggarwal; Prasanna Dhatavkar (Journal of Oral Biology and Craniofacial Research)
Introduction: The degree of conversion of dentin bonding agents contributes to the success of final restorations in adhesive dentistry. It is clinically relevant, as it is directly related to the overall bond strength that maintains these restorations in place and prevents marginal deterioration. However, Matrix metalloproteinases (MMPs) present within the dentin substrate have been known to have a deleterious effect on the bond stability, due to their collagenolytic activity. Inhibition of the effects of MMPs has been studied, and the use of a pre-treatment protocol that includes MMP inhibiting agents before bonding procedures has been explored, and has been found to increase bond strengths. However, the effect that MMP inhibitors have on dental adhesives has not yet been explored, particularly when being used in caries-affected-dentin (CAD). This study aims to report the degree of conversion of an 8th-generation dentin bonding agent in sound dentin (SD) vs caries-affected dentin after pre-treatment using MMP inhibitors. Materials & methods: 60 dentin discs were divided into groups of sound and affected dentin, and pretreated with either Cranberry extract or mulberry extract was applied to half of the discs in each group, followed by the application of an eight-generation bonding agent to the pre-treated discs, which were then light cured. The degree of conversion of the adhesive was calculated using ATR-FTIR spectroscopy. Results: The degree of conversion was found to be the highest in the samples of sound dentin which were pre-treated with Mulberry extract. Conclusion: Pre-treatment of the dentin with MMP inhibitors led to an increase in the degree of conversion in sound dentin but not in CAD.